(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines how the artistic representation of the world in Western literature is often created through imagination and fantasy, whereas in Eastern literary tradition extraordinary and unrealistic events typically appear in epics and fairy tales and are mainly connected to dream-related episodes. Such descriptive techniques are noticeable both in classical works and in modern texts. The study analyzes the use of the dream motif in Tog‘ay Murod’s novella “The Evening When the Horses Neighed.” The linguistic units found in the text form the basis for linguistically modeling the inner world of the protagonist. The article also discusses how modeling the world through language can be explored using texts from various functional styles.